Novel pyridinium oximes: synthesis, molecular docking and in vitro reactivation studies1. Issue 30 (3rd April 2015) - Pooja; Aggarwal, S.; Tiwari, A. K.; Kumar, V.; Pratap, R.; Singh, G.; Mishra, A. K.
<x xml:space="preserve">Abstract</x> A computational approach has been attempted for the screening of 4-pyridoxinium (4P) ring based reactivators for paraoxon inhibited AChE.